Peningkatan Keterampilan Menulis Cerpen Menggunakan Metode Mind Mapping Siswa Kelas VII SMP Islam Athirah Bukit Baruga Makassar - Fadhalani Tafdila S, Muh.; Usman, Usman; Rahim, Abd. (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This study aims to (1) describe the planning of using the Mind Mapping method to improve the writing skills of grade VII.4 students at SMP Islam Athirah Bukit Baruga Makassar; (2) describe the implementation of using the Mind Mapping method to improve the writing skills of grade VII.4 students at SMP Islam Athirah Bukit Baruga Makassar; (3) describe the assessment of using the Mind Mapping method to improve the writing skills of grade VII.4 students at SMP Islam Athirah Bukit Baruga Makassar. The type of research used is Classroom Action Research (CAR). To determine the improvement in short story writing skills using the Mind Mapping method, the research begins with planning the learning process by determining the teaching modules, the number of cycles, and the implementation model of Mind Mapping both in groups and individually. Then, the material on short story texts and their structures is explained. After that, the usage of the Mind Mapping method to structure stories is explained. Finally, students write stories by following the mind maps they have created to ensure the stories are well-structured. The assessment of short story writing skills using the Mind Mapping method shows that the average score in cycle 1 is 58.26. The average score in cycle 2 is 82.63 with a minimum completeness criterion (KKM) of 80. Thus, it can be concluded that there is a significant improvement between cycle 1 and cycle 2, where the method was initially used in groups and later individually.